EFFECTIVE METHODS FOR TEACHING THE PERIMETER OF TRIANGLES AND QUADRANGLES IN MATHEMATICS LESSONS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides a scientific and methodological analysis of effective methods for teaching the perimeter of triangles and quadrilaterals in mathematics lessons. The study reveals the pedagogical possibilities of using visual, practical, and interactive methods in forming the concept of perimeter. The effectiveness of game technologies in developing students' logical thinking and practical skills is also substantiated.